EXPLICIT INTRUCTION CORRELATION TO THE ACHIEVEMENT OFSTUDENTS IN FIQIH STUDENTS (Case Study at SMA Ma'arif Pandaan) - Syaifullah; Intan Robi'ah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2021)
on the reality that exists in schools, teachers have not maximally utilized the learning model, this is because teachers still use conventional learning. Then from the students who are accustomed to using conventional learning will feel depressed and lazy if suddenly they have to learn independently. So, for this we need a learning model that does not eliminate lectures, but is able to develop students' thinking power and independence and make students more interested in the material. This research belongs to the type of field research using a quantitative approach to the experimental type. Student learning outcomes before applied the model of explicit instruction with an average of 75 and aftermodels titerapkan explicit instruction average being 88.5. Themo del explicit instruction has a significant effect on the learning outcomes of students in class XI IPA 4 SMA Ma'arif NU Pandaan on the subject of jurisprudence on the matter of caring for bodies, because the results of the data output show that r table> r count is 17.045> 2.0332 and the value of Sig. 000 < 0.05 thus Ho is accepted and Ha is rejected, meaning that thelearning model explicit instruction affects student learning outcomes in fiqh subjects in class XI IPA 4 at SMA Ma'arif NU Pandaan.